2008
DOI: 10.1017/s0007485308006329
|View full text |Cite
|
Sign up to set email alerts
|

Host plant influence on susceptibility of Bemisia tabaci (Hemiptera: Aleyrodidae) to insecticides

Abstract: A resistance monitoring program conducted for the polyphagous whitefly, Bemisia tabaci (Gennadius), in Imperial Valley, CA, USA generated a large set of LC50s for adults collected from broccoli, cantaloupe and cotton crops over a four-year period. A vial bioassay and, subsequently, a yellow-sticky card bioassay produced similar temporal profiles of relative susceptibilities to the pyrethroid insecticide bifenthrin. Both bioassays revealed that whiteflies collected from broccoli were significantly less suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
(58 reference statements)
0
16
0
3
Order By: Relevance
“…The "preadaptation hypothesis" for insecticide resistance has been supported by surveys of the literature (11,12) although the comparisons drawn between herbivores and natural enemies or between chewing and sucking herbivores may be confounded by taxonomy, thus calling for other forms of experimental and observational evidence (12). It is now well accepted that herbivore exposure to different plant allelochemicals can affect the toxicity of pesticides (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Moreover, metabolic resistance to pesticides is known to commonly rely on the increased expression of one or more genes encoding detoxification enzymes and formal evidence that many of these detoxification enzymes can metabolize both plant chemicals and pesticides is accumulating (26,27).…”
mentioning
confidence: 99%
“…The "preadaptation hypothesis" for insecticide resistance has been supported by surveys of the literature (11,12) although the comparisons drawn between herbivores and natural enemies or between chewing and sucking herbivores may be confounded by taxonomy, thus calling for other forms of experimental and observational evidence (12). It is now well accepted that herbivore exposure to different plant allelochemicals can affect the toxicity of pesticides (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Moreover, metabolic resistance to pesticides is known to commonly rely on the increased expression of one or more genes encoding detoxification enzymes and formal evidence that many of these detoxification enzymes can metabolize both plant chemicals and pesticides is accumulating (26,27).…”
mentioning
confidence: 99%
“…Thus, Tian and Guo (1996) using different host plants as diet in Heliothis armigera, found differential responses of this insect to Deltamethrin. Castle et al (2009) found a high correlation between whitef ly populations developed in broccoli and high values of LC 50 to Bifenthrin. In the case of weeds (I and II) can be seen, that the host has a significant effect on the resistance to B. tabaci to Bifenthrin.…”
mentioning
confidence: 78%
“…Por tal motivo, el conocer el efecto del hospedero sobre las enzimas detoxificativas, puede ser utilizada como referencia en estudios de resistencia, dando evidencia teórica para el uso seguro y racional de plaguicidas (Castle et al, 2009). Debido a lo anterior el objetivo de este trabajo fue investigar el efecto de inducción enzimática detoxificativa, de seis plantas hospederas sobre la susceptibilidad de B. tabaci.…”
unclassified
See 2 more Smart Citations